Greek Astromythology: intersections between mythology history and modern Astronomy Education - Ferreira, Marcello; Orso da Fonseca, Marcos; Batista, Michel Corci; da Silva Filho, Olavo Leopoldino; Strapasson, Alexandre (Frontiers in Education, 2025)
This article provides a comparative assessment of the intersection between Greek Astromythology and Astronomy Education, as an interdisciplinary and intercultural contribution. The research is based on a qualitative assessment of narratives and concepts, using a brief systematic literature review to compile related academic production, with the objective of providing critical discussions on this intersection. The findings show that there is a broad diversity of themes in Astronomy that have their roots in Greek Astromythology: 174 items in total. Most stars related to Greek Astromythology, about 63%, were named in tribute to Greek culture, whereas approximately 36% of the findings correspond to elements belonging to the daily life of the Hellenic people. This shows that the Greeks' efforts to catalog various stars and think about the multiple aspects involving Astronomy resonate contemporarily and, therefore, it is imperative to contextualize the historical and cultural aspects involved in modern Astronomy science. In addition, the results identified a broad range of myths related to Astronomy, which demonstrate the significant contribution of Greek Astromythology to this science area. Hence, the use of mythology as a historical and cultural aspect of the visible constellations and planets can play a relevant contribution to scientific literacy and teaching, particularly in introductory courses of Astronomy, which are commonly developed in primary and secondary schools. Exploring this intersection at the school level can also enable the reflection, implementation, and evaluation of consistent teaching and learning indicators toward a critical education.